Computational Study of Flavonoid Compounds from Diplazium esculentum as Potential Anti-Acne Agents through Molecular Docking and ADMET Analysis - Zannah, Fathul; Fajeriyati, Nurul (Journal of Tropical Life Science, 2026)
Acne vulgaris is a common skin disorder influenced by multiple biological factors, including hormonal regulation, microbial activity, and inflammatory processes. The overactivation of androgen-regulated pathways contributes to excessive sebum production, which plays a central role in acne development. Although synthetic anti-acne drugs are widely used, their prolonged application may cause adverse effects, prompting growing interest in natural compounds as alternative therapeutic candidates. Diplazium esculentum, a medicinal fern traditionally used in Indonesia, has been reported to possess antibacterial activity; however, its molecular potential as an anti-acne agent remains insufficiently explored. This study aims to computationally investigate flavonoid compounds derived from Diplazium esculentum as potential anti-acne agents by evaluating their molecular interactions and pharmacokinetic properties. The research focuses on a molecular docking approach combined with pharmacokinetic and toxicity prediction to provide preliminary insights at the molecular level. Flavonoid compounds identified from liquid chromatography–mass spectrometry profiling, including apigenin, genistein, daidzein, and naringenin, were selected as ligands for computational analysis. Molecular docking simulations were performed to predict the interaction between these compounds and the androgen receptor, a key molecular target associated with hormone-regulated sebum production. In addition, pharmacokinetic and toxicity properties were evaluated using in silico absorption, distribution, metabolism, excretion, and toxicity prediction tools to assess drug-likeness and safety profiles. The results demonstrated that all evaluated flavonoids exhibited favorable binding interactions within the ligand-binding domain of the androgen receptor, with interaction patterns comparable to those of a reference compound. Pharmacokinetic predictions indicated acceptable absorption characteristics and low toxicity risk for the selected flavonoids. In conclusion, this computational study highlights the potential of flavonoid compounds from D. esculentum as promising natural candidates for anti-acne applications. The findings support the use of molecular docking and pharmacokinetic prediction as effective preliminary approaches for exploring drug potential and provide a scientific basis for further experimental validation.